Electromagnetic Shielding Techniques in the Wireless Power Transfer System for Charging Inspection Robot Application - Chaoqun Jiao; Yang Xu; Xiang Li; Xiumin Zhang; Zhibin Zhao; Chengzong Pang (International Journal of Antennas and Propagation)
Aiming at eliminating the leakage of magnetic fields from the wireless power transfer (WPT) system, the structural and working characteristics of the WPT system for the inspection robot are analyzed and an electromagnetic shielding method combining passive shielding and active shielding is proposed in this paper. Firstly, we simulated the magnetic field distribution of the WPT system in Maxwell. Secondly, passive shielding is configured in the WPT system, and the material, size, and position of the passive shielding are studied. Then, we add active shielding to areas where passive shielding cannot achieve a good shielding effect. Based on the analysis and summary of the two methods, we shield the WPT system in the horizontal direction with the appropriate size and distance of aluminum plate, and in the vertical direction, we use the active shielding coils. Simulation and experimental results show that the scheme only slightly reduces the transmission efficiency of the system (from 80.2% to 77.6%), but the shielding ability is 34.06% higher than that of only aluminum plates. The excellent effect of the proposed shielding method is verified in our experiment.